1996
DOI: 10.1152/ajprenal.1996.271.2.f365
|View full text |Cite
|
Sign up to set email alerts
|

Basal nitric oxide production curtails arteriolar vasoconstrictor responses to ANG II in rat kidney

Abstract: Experiments were performed to test the hypothesis that renal arteriolar vasoconstrictor responses to angiotensin II (ANG II) are curtailed through a mechanism that involves stimulation of endogenous nitric oxide (NO) synthesis. The in vitro blood-perfused juxtamedullary nephron technique was exploited to monitor arteriolar lumen diameter responses to exogenous ANG II before and during treatment with the NO synthase inhibitor N omega-nitro-L-arginine (L-NNA). Under control conditions, 1 nM ANG II reduced affere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…These observations were consistent with the direct observations that AVP stimulated NO production in the epithelial cells of inner medullary collecting ducts (IMCD) as determined by fluorescent microscopy (67) and other reports that AVP stimulated increases of urinary cGMP concentrations (103) and that the inhibition of NOS acutely enhanced systemic pressor responses to AVP (35,109).…”
Section: Acute Counterregulatory Action Of Renal Medullary No On Circsupporting
confidence: 91%
See 2 more Smart Citations
“…These observations were consistent with the direct observations that AVP stimulated NO production in the epithelial cells of inner medullary collecting ducts (IMCD) as determined by fluorescent microscopy (67) and other reports that AVP stimulated increases of urinary cGMP concentrations (103) and that the inhibition of NOS acutely enhanced systemic pressor responses to AVP (35,109).…”
Section: Acute Counterregulatory Action Of Renal Medullary No On Circsupporting
confidence: 91%
“…Reduction of tissue NO production with NOS inhibition was found by some investigators to enhance ANG II-induced reduction of renal blood flow (1) and to potentiate the vasoconstrictor effects of ANG II in isolated perfused kidneys (105). Similar findings were obtained using the in vitro perfused juxtamedullary preparation (35) and in isolated perfused afferent arterioles (37). Others found no evidence of enhanced vasoconstriction to either ANG II or NE after NOS inhibition using a perfused split kidney juxtamedullary preparation when vessel diameter was restored to normal by sodium nitroprusside (35), or in studies using an in vitro hydronephrotic kidney preparation (87).…”
Section: Acute Counterregulatory Action Of Renal Medullary No On Circmentioning
confidence: 56%
See 1 more Smart Citation
“…Comparing S1P with many other common vasoconstrictors on afferent arteriolar reactivity shows that the S1P-mediated vasoconstriction of afferent arterioles is less potent than the vasoconstriction induced by endothelin 1, 47 but similar to the vasoconstriction induced by other GPCR agonists, such as angiotensin II, 35,48 arginine vasopressin, 48 and NE, 35 whereas S1P is more potent than ATP. 49 It requires approximately 10 pM of endothelin-1, 6 nM of angiotensin II, 70 nM of S1P, 200 nM of arginine vasopressin, 300 nM of NE, and 100 mM of ATP to achieve a 25% reduction of afferent arteriolar diameters.…”
Section: Discussionmentioning
confidence: 96%
“…10 Short-term studies by others also support the conclusions that Ang II releases NO and that inhibition of NOS activity enhances the renal vasoconstrictor actions of Ang II in rat kidneys. 23 Ang II infusion has been reported to elevate renal excretion of nitrate and/or nitrite 14 and increase cGMP concentration in renal cortical interstitial fluid. 13 Madrid et al 24 have shown that renal NO production buffers Ang II effects on pressure-natriuresis and on the CBF and papillary blood flow.…”
Section: Initial Responses To Intravenous Ang II Infusionmentioning
confidence: 99%